Looking back - looking forward: a novel multi-time slice weight-of-evidence approach for defining reference conditions to assess the impact of human activities on lake systems - Hollert, Henner; Rösch, Manfred (The science of the total environment, 2018)
Lake ecosystems are sensitive recorders of environmental changes that provide continuous archives at annual to decadal resolution over thousands of years. The systematic investigation of land use changes and emission of pollutants archived in Holocene lake sediments as well as the reconstruction of contamination, background conditions, and sensitivity of lake systems offer an ideal opportunity to study environmental dynamics and consequences of anthropogenic impact that increasingly pose risks to human well-being. This paper discusses the use of sediment and other lines of evidence in providing a record of historical and current contamination in lake ecosystems. We present a novel approach to investigate impacts from human activities using chemical-analytical, bioanalytical, ecological, paleolimnological, paleoecotoxicological, archeological as well as modeling techniques. This multi-time slice weight-of-evidence (WOE) approach will generate knowledge on conditions prior to anthropogenic influence and provide knowledge to (i) create a better understanding of the effects of anthropogenic disturbances on biodiversity, (ii) assess water quality by using quantitative data on historical pollution and persistence of pollutants archived over thousands of years in sediments, and (iii) define environmental threshold values using modeling methods. This technique may be applied in order to gain insights into reference conditions of surface and ground waters in catchments with a long history of land use and human impact, which is still a major need that is currently not yet addressed within the context of the European Water Framework Directive.
Gesehen am 25.10.2019